Proton pump inhibitor: a risk factor for spontaneous bacterial peritonitis in Indian cirrhotics decompensated with ascites - Rajender, Akash; Choudhary, Priyanka; Mathur, Saumya; Bhargava, Rajat; Upadhyay, Shalini; Nepalia, Subhash (International Journal of Research in Medical Sciences, 2019)
Background: Spontaneous bacterial peritonitis (SBP) is common complication of cirrhosis caused by bacterial translocation. Bacterial colonization and overgrowth may occur in GI tract on suppression of gastric acid secretion. Beta-blockers have been postulated to reduce intestinal permeability. There is no significant Indian study to evaluate association of PPI with SBP in cirrhotic ascites. We aimed to assess the effect of PPI in cirrhotic patients decompensated with ascites. Methods: A retrospective case control study (January 2016 to April 2018), evaluated subjects with cirrhosis and ascites. Two study groups of cirrhotic subjects with and without SBP were formed. In each of the two study groups, 143 subjects, were enrolled by matching for age, year of admission, Child-Pugh-Turcotte (CTP) class after considering the inclusion and exclusion criteria. PPI use and various other correlates were compared in both study groups. SPSS ver 24.0 was used for statistical analysis. Results: About 69.23% subjects were using PPI prior to admission in SBP group, which was significant compared to only 31.47% in cirrhotics without SBP (p 0.003). On multivariate analysis PPI use was an independent risk factor for SBP (OR 2.24, 95% CI: 1.01-4.24; p value 0.033) and beta blocker use was protective (OR 0.58; 95% CI: 0.4-0.8; p 0.001). Conclusions: PPI use doubles the risk of development of SBP in cirrhotics decompensated with ascites. In contrast, Beta blockers use significantly lowers the risk of SBP.